NUMBER OF SEEDS PER HOLE AND PLANTING DISTANCE GOGO INFLUENCE OF RICE ( Oryza sativa L. ) WITH System of Rice Intensification ( SRI ) IN THE DRY LAND - Christanto, Hery; Sri Agung, I Gusti Ayu Mas (Bumi Lestari, 2014)
Water availability is a major limiting factor to the growth and yield of rainfed rice.  System of Rice Intensification (SRI), which is an efficient method of planting rice, particularly in the use of water, number of seeds per hill and time of transplanting seedlings, has been applied generally in irrigated rice but it is rarely practiced in rainfed rice. A field experiment, which was aimed to study the effect of number of seed/hill and variation of plant spacing on the growth and yields of rainfed rice with SRI (System of Rice Intensification), was conducted during dry season from April until September 2012. The location was at Patemon Village, District of Seririt, Buleleng Regency, Bali, at the altitude of 100 meter asl. In this experiment a completely randomized block design was used and the treatment were arranged factorially. The first factor was the number of seeds (1,2,3 and 4)/ hill and the second one was the plant spacing (20 cm x 20 cm, 25 cm x 25 cm and 30 cm x 30 cm). All treatments were replicated three times. The results of the experiment showed that the interaction between one seed/hill and plant spacing of 30 cm x 30 cm resulted in significantly (P<0.05 and P<0.01)  the highest fresh (4.387 ton/ha) and oven dry weight of grains (3.633 ton/ha), oven dry weight of 1000 grains (20.920 g) and the harvest index (31.163%). The gross margin analysis indicated that the variable costs were higher than the gross income for all treatment, due to high cost of watering
Keywords: System of Rice Intensification (SRI), Rainfed Rice (Oryza sativa L.), Number of Seed, Plant Spacing , Dry Land Farming